Gender Disparities in Access to Financial Services and its Implications for Poverty Alleviation in Malawi - Mnthali, Felix (International Journal of Poverty, Investment and Development, 2024)
Purpose: The aim of the study was to assess the gender disparities in access to financial services and its implications for poverty alleviation in Malawi. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study have consistently shown that women face greater obstacles in accessing financial services compared to men, including limited access to credit, savings, insurance, and other financial products. These disparities are rooted in various factors such as cultural norms, legal restrictions, lack of collateral, and limited financial literacy among women. As a result, women often have less control over household finances and are more vulnerable to economic shocks, trapping them in cycles of poverty. Addressing gender disparities in financial access is crucial for achieving sustainable development goals, as empowering women economically has been linked to higher household income, improved health and education outcomes, and overall poverty reduction. Implications to Theory, Practice and Policy: Feminist theory, capability approach and intersectionality theory may be used to anchor future studies on assessing the gender disparities in access to financial services and its implications for poverty alleviation in Malawi. Implement gender-responsive financial literacy programs that are tailored to the specific needs and constraints faced by women in different contexts. Enact and enforce gender-sensitive policies and regulations within the financial sector to eliminate discriminatory practices and promote women's equal access to credit, savings, insurance, and other financial services.